Oferta académica de la Carrera de Enfermería de la Universidad Estatal de Bolívar relacionada con la Empleabilidad de los y las graduadas en la zona 5. año 2018-2020 - Remache Escobar, Luis Miguel (2022)
The research carried out seeks to know important aspects of current employability needs from the perspective of graduates of the nursing career of the State University of Bolívar. Nursing of the State University of Bolívar with the employability of graduates in Zone 5 in the period 2018-2020. To comply with these, a methodology of quantitative approach, of the descriptive type, of non-experimental design and of cross-sectional design, was designed, applying two closed questionnaires to two sample populations of graduates of the nursing career of the University of Bolívar in the years 2018 a2020 and companies in Zone 5. As a result, it was identified that out of a population of 84 graduates, 77 were working in different institutions, mainly first and second level. Regarding the identification of competencies, it was recognized that for some entrepreneurs the performance of the professionals was not qualified as excellent. In conclusion, it was obtained that from the perspective of most of the student body there is a relationship between what is demanded by the labor market and academic training and what is required by the Ministry of Public Health, in position to what was stated by employers where 60% believed that the academic profile of nursing professionals was good according to their requirements and 40% of employers believed that it was excellent. Therefore, it is advisable to improve the teaching and learning processes related to the areas of pediatrics, surgery and internal medicine and interpersonal communication skills, critical capacity and emotional management in order to train more competitive nursing professionals in the labor market. Keyword: Employability, Nursing Career, Academic Offering